Hybrid Model of Artificial Neural Network with Orthogonal Regularization - Didmanidze, Ibraim; Kakhiani, Gregory (International Scientific-practical Conference: „Modern Challenges and Achievements in Information and Communication Technologies“ Transactions, 2025)
The paper proposes a new method for forecasting foreign exchange time series, which improves accuracy and robustness against noise and non-linear structures present in the data. The main innovation is the integration of an orthogonal transformation layer (e.g., Fourier, Wavelet, PCA-based) with traditional RBF and MLP layers. This hybrid approach ensures optimal data preprocessing, reduces feature correlation, and minimizes the conditional number of the Jacobian matrix. A significant theoretical and practical contribution is the introduction of orthogonal regularization, which directly controls the preservation of the orthogonality of the transformation matrix during learning. Experimental results on three major currency pairs (EUR/USD, GBP/USD, USD/JPY) confirm that the proposed hybrid model significantly reduces the Mean Squared Error (MSE) by 12–15% compared to classical models and accelerates convergence by 20–30%. The paper highlights this model's superiority over LSTM and CNN networks in terms of its robustness and computational efficiency